# 3h-4=h+2

Would like to know the answer and how to do the sum

Hi PhilThe key is to always do the same thing on both sides of the equals sign.3h-4=h+2Subtract h from both sides: 3h-4-h=h+2-hto give: 2h-4=2Add 4 to both sides: 2h-4+4=2+4To give: 2h=6Divide by 2 on both sides to give your answer: h=3Then you can check to see if this works in the original equation:3h-4=h+2If h=3, then...       3x3-4=3+2Do the multiplication first: 9-4=3+2      =          5=5
biology_teacher
15 September 2013
3h-4=h+2taking the hs to the same side we get, 3h-h-4=22h=2+4therefore 2h=6and h=3
ceexbee
19 September 2013
Hello,First I'll talk through the general principles for solving any linear equation such as the one you have shown and then I'll show how to apply that to this particular example.Solving an equation is about getting to the point where you can write x = specific number (or in this case h=) or another way to think about it is that you need to get x on its own on one side of the equation.To do this we need to be able to remove the numbers that are with the x.  It helps to think of an equation as a pair of old fashioned weighing scales that you must keep in balance all the time.  To keep the balance whatever you do to one side of the equation you must do to the other - note the sides of the equation are separated by the = sign.  To decide how to remove an number you need to do the opposite of what it is currently doing so if the number is added on then you need to take it away or if the number is multiplying the x then you need to divide.So to sum up the 3 key principles of solving a linear equation:1.  Get x on its own2.  Do the same to both sides3.  Do the opposite to remove a numberHere's how this works for your particular example.First we need to get all the h's on one side, so we will remove the h from the far side by - h from both sides.3h - 4 = h + 2-h          -h2h - 4 = 2Now we will remove the -4 by adding 4 to both sides.+4          +42h = 6Finally we will remove the 2 by dividing both sides by 2/2      /2h = 3
10:04 on 20/09/13
22 September 2013
Hello there Phil,To solve this equation we need to make everything =0To do this we move evrything to one side
Jessie O.
22 September 2013
sketch-1.svg
Jessie O.
22 September 2013
3h - 4 - h = h + 2 - h2h - 4 = 22h - 4 + 4 = 2 + 42h = 6 h = 3
elrech60
23 September 2013
3h -4 = h+23h - h = 4 + 2h(3-1) = 62h=62h/2 = 6 /2h = 3
24 September 2013
3h-4=h+2subtract a h from each side2h-4=2add 4 to each side2h=6divide by 2h=3
Kerry M.
03 October 2013
The best way to solve this equation is to move all of the h bits to one side of the equation and all the number bits to the other sideIn this equation I would firstly move the 4 from left hand side to the right hand side (when you do this you do the opposite so to move -4 over you add it)So 3h = h + 2 + 4so  3h = h+ 6 (adding the 2 and the 4)Next move the h from the right hand side to the left (as it is a +h to move it you do the opposite and take it awaySo 3h - h = 6So 2h =6  (3h - h =2h)Next move the 2 to the other side to leave h on its ownTo do this do the oppostie of multiplying by 2 which is to divideSo h = 6/2So h =3This is the answer
fully
10 October 2013
As 'h' is the variable, you would want to leave it alone at one side, while having all the given number at the other side.Substract 'h' from both sides: you would have (3h-h) - 4 = (h-h) + 2And that is 2h -4=2Now add 4 to both sides to leave 2h alone on the left hand side.2h-4+4=2+42h=6Divide both sides by 2.h=6/2h=3
lolafinn
15 October 2013
Keep it simple Kiss numbers with letters on 1 side numbers with no letters on the other 3h-1h. On one side 2+4 on the other 3h-1h=2+4 2h=6 h=3
carolanneelliott
17 October 2013
All you have to do is  re-arrange this equation. A good way is to first get all the "h" stuff on one side of the equation, and all the other "non-h" stuff on the otherside.    3h-4=h+2I add 4 to both sides       3h-4+4=h+2+4to get                              3h = h +6 (Remember, that when balancing equations, whatever you do to one side you must also do to the other side)Then, to get all the "h" stuff on one side, you mus remove the h on the right hand side. To do this, remove h from both sides      3h - h =h+6-hwhich simplifies to  2h = 6Now, we have all the "h" stuff on one side, as required, and all the "non-h" stuff on the other side. We now know what 2h is. But we want to know what h is. Everything is twice as big as we want it to be, so all we have to do is divide both sides by two to get  h=3
Miriam L.
23 October 2013
collect h on left and numbers on right=> 3h-4=h+2=> 3h-h=4+2=> 2h=6=> h=3If you ever want any tutoring help please do contact me, I'm the cheapest around! :)
Rulank K.
27 October 2013
make h the subject by taking h from the right to the left to get:2h-4=2 then bring 4 to the other side( you add 4 to cancel the +/-)2h=6 divide by 2 work out hh=3
cheese123568
28 October 2013
triptiagarwal
28 October 2013
'Equality', put it {A=B}, is a RULE.This is the premier fondamental item to retain in case you have to work with an equality or 'equation' - like the one upper there, imposed hypothesis: This { 3h - 4  =  h + 2 }.Then comes a four-in-ONE PROPERTY of the equality:You can add (operator 'plus'), substact (operator 'minus'), multiply (operator 'time' or 'times'), divide (operator 'slash'); you can hence 'operate' an euation by all four 'operators', as much as you want it, without breaking the law (of equality) [proper and more precise math lingo for this saying is 'without violating the equality'],... but this property and permission has got one CONDITION: The operation must be undertaken using same second value or character, and SIMULTEANOUSLY ON BOTH MEMBERS (the right, the left) of the equation:Supposing your equation be { A = B }, you can turn it to either:-Using 'plus' C:   A + C  =  B + C.or:  -Using 'minus' C:   A - C  =  B - C.or:  -Using 'times' C:   A * C  =  B * C.or:  -Using 'slash' C:   A / C  =  B / C.PS: It also works with a say-fourth operator:  The 'power' (which writes '^').  Eg. on same {A=B}:  It will write { A^C = B^C }./You now have the tailored one-and-multiple tool (alike a Swiss knife) to arrange any equation in whatever form you may want to turn it./Make a try of it ... on modifying the syntax of the hypothesis up here, the { 3*h - 4  =  1*h + 2 } the way the question wants it ?/Good will!  And please report to me on your making  and/or  feel free to ask me any question!Jean
scolaire92
29 October 2013
make h the subject by taking h from the right to the left to get:2h-4=2 then bring 4 to the other side( you add 4 to cancel the +/-)2h=6 divide by 2 work out hh=3
triptiagarwal
29 October 2013
Step 1.  Put all the numbers on one side of the equation, so 3h-4=h+2 becomes 3h=h+2+4 (the 4 is positive on the left, so becomes negative on the right).Step 2.  Gather the letters together, so 3h=h+2+4 becomes 3h-h = 2+4 (similar principles, h is positive on the right, becomes negative when you move it to the left).Step 3.  Simplify the terms on both sides of the equation.  So, 3h-h=2+4 becomes 2h=6Step 4. You want to find h, but at the moment you know that 2h=6, so divide both sides by 2, so 2h/2 = h whereas 6/2 = 3.  Your equation can now be simplified to h=3.Hope that helps.
dr._clare
31 October 2013
Hi there..for this question you need to move the terms around..in this question I would move the h to the other side of the equation..If it is +h on the right of the = then it will change to subtract as it moves over to the other side..this means you will have3h-h-4=2If you take a h away you ill be left with 2h-4=2This time we can move the -4 to the other side and as it move over the = it will change to +4 so now we have 2h=2+4....so..2h=6..as we are trying to get h on its own we need to move the 2 this time..throw it over to the oher side and as it is being multiplied, as it moves over it changes to divide! ...we now have h=6divide2..the answer for h is 3.........to check you can put this answer into the formula and calculate if both sides balance and are equal...good luck with the algebra!
Sharon B.
09 November 2013
3h-4=h+23h-h=2+42h=6h=6/2h=3
Georgina W.
15 November 2013
3h-4=h+23h-h=2+42h=6h=3
anurag5384
15 November 2013
First look at the question and find out the variable.here variable is h.So for solving such questions bring the variable to one side(either right or left ) = sign.Then apply addition/subtraction/divison/multiplication,whatever is applicable.Here3h-4=h+2variable is h so bring it to left side3h-h=2+42h=6h=3
anurag5384
15 November 2013
You need to balance the equation so the first thing you should do is move similar aspects to one side of the = sign.Step one3h - 4 +4 = h +2 +4This will give you3h = h + 6You then need to move the h so it is on the same side.3h-h = h-h +6This gives you:2h = 6Last step to get the h completely alone so you would divide 2h by 2 and 6 by 2 giving you:h = 3
beckyj78
16 November 2013
As below but imagine that your equation is a pair of old fashioned weighing scales. Each side needs to be balanced, so if you have addition on one side and you move it to the other side you need to make it subtraction.
Emma N.
26 November 2013
3 rules for soving linear equations1.  Goal is to get the letter on its own equal to a number so in this case h = number.2.  You must always do the same to both sides of the equation - the = sign separates the sides.3. You decide what to do by doing the OPPOSITE of what is being done so if you want to remove a + 6 you would - 6 or if you want to remove the 3 from 3x, which means 3 times x, you would divide by 3 and so on.In this specific example your first step is to get h's on just one side - you always remove the lower one, here the single h.  To do this take h away from both sides to get2h -4 = 2Now get rid of the -4 by adding 4 to both sides to get2h = 6Finally divide both sides by 2 to geth = 3
10:13 on 16/11/13
26 November 2013
The equation is equivalent to:2h=6h=3
tymek
27 January 2014
Get all the h's to one side by subtracting h from each side.2h-4=2Get all the numbers on the other side by adding 4 to both sides.2h=6get one h by dividing both sides by 2.h=3
Chris T.
27 January 2014
If there is one variable, always try to get that variable on one side of the equation, remember what you do to one side of the equation, you must do to the other. so to get rid of the "-4" on the left, you must "+4" to both sides, this gives:3h=h+6if you take away h from both sides2h = 6divide both sides by 22h/2=6/2h=3
mlin
28 January 2014
Add 4 to both sides.This is really so we can get rid of the '-4' (minus 4) on the left hand side of the equation.You will be left with:3h=h+2+4So3h=h+6Then subtract 'h' from both sidesThis leaves you with3h-h=6Then2h=6Next..Divide both sides by 2 (this is to get rid of the 2 on the left really)Soh=6 divided by 2So h=3Make sense?
Steve R.
29 January 2014
Assuming you want to solve for h you want to collect all the terms containing a factor of h on one side of the equation and all other terms on the other side of the equation. So for your example we have 3h -4 = h +2.Let's first gather all terms containing h onto the left side of the equation:(as we bring a term from one side of the equation to the other we must change it's sign so h becomes -h) this gives us:3h -4 -h = 2but 3h -h = 2h so we now have:2h -4 = 2Now we want to collect all terms that do not contain h onto the right had side of the equation, again when we move a term to the other side of the equation we must reverse it's sign so -4 becomes +4. Now we have:2h = 2+4so2h = 6Now we want to get a term just containing h on the Left hand side of the equation so we divide both sides of the equation by 2:h = 6/2h = 3.
mathmom
30 January 2014
See whiteboard for solution.the rule for moving values from one side of the equals sign to the other is to change its sign so a h moved over to the left handside becomes -h and the 4 over to the right becomes +4.you can also think of it as subtracting both sides by h or adding 4 to both sides. remember whatever you do to one side you must do to the other otherwise it is not equal.
matt_thomas
30 January 2014
sketch-2.svg
matt_thomas
30 January 2014
In order to answer this question, you need to group similar terms (i.e. terms containing h and terms not containing h in this example) either side of the = sign. I.e. take h away from both sides, to leave 2h-4 = 2Add 4 to both sides, to leave 2h = 6.Now divide both sides by 2 to give h = 3.
mr1303
31 January 2014
This is an algebra problem - it uses letters as well as numbers. In this equation you are looking for the value of h.Your starting point: 3h - 4 = h + 2This is an equation (has an equals sign) with a left side (LS) and a right side (RS)Put all the letters on the same side, so h on the RS changes to - h on the LS.....like this3h - h - 4 = 2Put all the numbers on the same side, so - 4 on the LS changes to 4 on the RS.....like this3h - h = 2 + 4Now do the adding/taking away....like this3h - h = 2h    and 2 + 4 = 6So ...... 2h = 6 which means that h = 3I hope this helps :)
cajones
03 February 2014
In this question h represents a number that you don't know yet, and you want to ultimately rearrange it and stuff to get to the stage h=?? and then you'll know what h is.First of all, get the h on one side of the equation. so here we shall minus h from both sides which gives you:2h-4=2Then to simplify more add 4 to both sides2h=6Then because we have 2h on one side, and we want to get it to just h=??, we divide by two:h=3 and you have your answer. :)
sophiesimone
03 February 2014
3h - 4 = h + 2Now take the -4 to the right hand side whilst taking the +2 to the left hand side. By putting it to the other side you must change the signs to act the opposite from the original i.e. changing + to - and divide to multiplication and/or visa versa. This gives:3h - h = 2 + 4solving gives:2h = 6(note: it is 2 multiplying by that h so putting it to the other side makes it act to the opposite of that making it become divide)Therefore:h = 6/2 h = 3
armankarim
06 February 2014
5
Kanise
21 May 2021